Severe systemic disorder in a 5 months old child: A case of early systemic lupus erythematosus? - Grabhorn, Enke; Englert, Cornelia; Geisler, Benjamin; Ganschow, Rainer (Journal of Pediatric Infectious Diseases, 2006)
A 5-month-old girl developed intractable cerebral seizures and a global mental and motor retardation after a scheduled hexavalent vaccination. In the following years, recurrent fever, hepatosplenomegaly, and a pancytopenia indicated other organ system involvement. At the age of 4 years the diagnosis of a severe systemic autoimmune disorder was made, defined by highly elevated antinuclear antibody (ANA), smooth muscle antigen (SMA), extractable nuclear antigen, and decreased complement factors C3c and C4. Moreover, a low B cell count and an IgA and IgG2 subclass deficiency were found. After initiation of an immunosuppressive therapy as well as monthly intravenous immunoglobulin application, the clinical situation improved dramatically. Despite therapy and clinical improvement, there is still an intermittent elevation of ANA and SMA as well as decreased complement C4, a persistent low B cell count and an IgA deficiency. We propose the possibility of an underlying primary immunodeficiency with subsequent development of a severe systemic autoimmune disease possibly triggered by routine vaccination. The clinical features and laboratory tests are consistent with a systemic lupus erythematosus or lupus-like syndrome.
Keywords: Systemic lupus erythematosus; autoimmunity; immunodeficiency